Prevalence of malnutrition risk and its association with mortality: nutritionDay Latin America survey results. Issue 9 (September 2021) - Correia, M. Isabel T.D.; Sulo, Suela; Brunton, Cory; Sulz, Isabella; Rodriguez, Dolores; Gomez, Gabriel; Tarantino, Silvia; Hiesmayr, Michael
Summary: Background & aims: Across the globe, the prevalence of hospital malnutrition varies greatly depending on the population served and on local socioeconomic conditions. While malnutrition is widely recognized to worsen patient outcomes and add financial burdens to healthcare systems, recent data on hospital malnutrition in Latin America are limited. Our study objectives were: (1) to quantify the prevalence of malnutrition risk in Latin American hospital wards, and (2) to explore associations between nutritional risk status, in-hospital food intake, and health outcomes. Methods: On nutritionDay (nDay), a specific day every year, hospital wards worldwide can participate in a one-day, cross-sectional audit. We analyzed nDay data collected in ten Latin American countries from 2009 to 2015, including demographic and nutrition-related findings for adult patients (≥18 years) from 582 hospital wards/units. Based on patient-reported responses to questions related to the Malnutrition Screening Tool, we determined the prevalence of malnutrition risk (MST score ≥2). We also summarized patient-reported food intake on nDay, and we analyzed staff-collected outcome data at 30 days post-nDay. Results: The prevalence of malnutrition risk in the Latin American nDay study population (N = 14, 515) was 39.6%. More than 50% of studied patients ate one-half or less of their hospital meal, ate less than normal in the week before nDay, or experienced weight loss in the prior three months. The hospital-mortality hazard ratio was 3.63 (95% CI [2.71, 4.88]; P < 0.001) for patients eating one-quarter of their meal (compared with those who ate the full meal), increasing to 6.6 (95% CI [5.02, 8.7]; P < 0.0001) for patients who ate none of the food offered. Conclusions: Based on compilation of nDay surveys throughout Latin America, 2 of every 5 hospitalized patients were at risk for malnutrition. The associated risk for hospital mortality was up to 6-fold higher among patients who ate little or none of their meal on nDay. This high prevalence showed scant improvement over rates two decades ago—a compelling rationale for new focus on nutrition education and training of professionals in acute care settings.